Understanding Surface Flashover in Helium Gas Cooled High Temperature Superconducting Devices. Issue 1 (March 2020) - Al-Taie, A; Cheetham, P; Kim, C H; Park, C; Graber, L; Pamidi, S V
Abstract: Surface flashover voltage on solid insulators in gas cooled superconducting power devices is studied. The relationship between the surface flashover voltage and the dielectric strength of the gas media is established. Analysis of the data on surface flashover voltage measurements on cylindrical samples made of high-pressure fiberglass laminate (G10) in three different gas media with varying dielectric strength and pressure showed a positive correlation between the surface flashover voltage and the dielectric strength of the gas both at room temperature and 77 K. The positive relationship, however, is not linear. The results suggest that using gas media with higher dielectric strength, employing higher pressure, and lowering temperature in HTS power devices leads to higher surface flashover voltages and higher operating voltages because surface flashover is usually the limiting voltage in devices that use solid support structures and possess voltage gradients.